Increased Initial Reading Through Picture Word Cards - Syaripah, Latipah (Jurnal Indonesia Sosial Sains, 2024)
The purpose of this research is to address the need for fun and student-centered education, which is essential in the 21st century. Active learners are crucial for enhancing student engagement and positively impacting their lives. The specific focus is on improving the initial reading skills of grade III students at SDN Caringin II, which have been observed to be low. The research utilizes Classroom Action Research (PTK) following the model developed by Kemmis and Taggart, implemented in two cycles with two actions each. Data collection involves observation and the use of a rubric to assess reading skills. The results demonstrate that the use of picture word cards effectively enhances students' initial reading abilities, with 83% of students meeting the criteria for initial reading proficiency across various indicators. These indicators encompass aspects such as letter recognition, vowel and consonant combinations, and reading comprehension of sentences and paragraphs. Consequently, the research recommends the incorporation of picture word cards as an alternative learning method to cultivate and strengthen students' initial reading skills.